Kegiatan Bernyanyi di Depan Kelas dalam Mengembangkan Kemampuan Motorik Kasar Anak Kelompok B (5-6 Tahun) di TK Aisiyah 2 Palembang - Farah Yanuarita; Evia Darmawani; Padilah Padilah (Departement of Mathematics Education, 2023)
This study aims to deermine the development of gross motor skills in group B children (5-6 years) in Aisiyah 2 Palembang. This research is a type of experimental quantitative descriptive research method. Namely by using singing activities in front of the class to develop gross motor skills in children at kindergarten Aisiyah 2 Palembang. The results of this study indicate that there is an effect of singing activities in front of the class on the gross motor development of children in kindergarten Aisiyah 2 Palembang. Then it is obtained that the significant value (2-tailed) is 0.000 because the signifivant value is less than 0.025, then Ho is rejected, meaning Ha is accapted, so there is a significant difference in singing activities in front of the class on gross motoric development of children in kindergarten B Aisiyah 2 Palembang.